Analisis Marketing 4P Alam Sutera - Noyanta Luga; Evi Enitari Napitupulu; Mega Sihombing; Henokhi Agustus; Billy Dio (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
This research aims to test the analysis of the influence of the 4p marketing mix and service quality on customer purchasing decisions (case study of IKEA Alam Sutera, South Tangerang). This research consists of five independent variables, namely product, place, price, promotion and service quality, while customer purchasing decisions are the dependent variable. IKEA, Alam Sutera has a vision to create a better everyday life for people by offering a range of products that are well designed, functional and affordable. According to Deloitte-global-powers-of-retailing (2015), the problem faced by IKEA is its revenue position which is ranked 5th. This shows that they still need to improve their strategy in order to attract and make consumers decide to buy. . Primary data was collected using a questionnaire from 140 respondents to IKEA Alam Sutera, South Tangerang (Supranto, 2001). The research results show that product and place do not have a partially significant influence on customer purchasing decisions, while price, promotion and service quality have a partially significant influence on customer purchasing decisions. Apart from that, the five independent variables have a significant influence simultaneously on the dependent variable. The predictive ability of the five variables on customer purchasing decisions in this research is 29%. Meanwhile, the remaining 71% was influenced by other factors not included in this research.